2019
DOI: 10.3390/ijms20040798
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Implications of Natriuretic Peptides in the Protection from Hypertension and Target Organ Damage Development

Abstract: The pathogenesis of hypertension, as a multifactorial trait, is complex. High blood pressure levels, in turn, concur with the development of cardiovascular damage. Abnormalities of several neurohormonal mechanisms controlling blood pressure homeostasis and cardiovascular remodeling can contribute to these pathological conditions. The natriuretic peptide (NP) family (including ANP (atrial natriuretic peptide), BNP (brain natriuretic peptide), and CNP (C-type natriuretic peptide)), the NP receptors (NPRA, NPRB, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 86 publications
0
47
0
1
Order By: Relevance
“…Intriguingly, recombinant human brain natriuretic peptide (rhBNP) succeeded to reduce acute lung injury in canine models 19 , 20 . In addition , recent studies showed that brain natriuretic peptides (BNP) might provide a significant protection against target organ damage by inhibition of the oxidative stress 21 . Among the signaling pathways that are activated by the ROS are the Nuclear Factor Kappa B (NF-κB) and the mitogen activated protein kinase (MAPK) pathways that control diverse cellular events such as inflammation, proliferation and apoptosis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, recombinant human brain natriuretic peptide (rhBNP) succeeded to reduce acute lung injury in canine models 19 , 20 . In addition , recent studies showed that brain natriuretic peptides (BNP) might provide a significant protection against target organ damage by inhibition of the oxidative stress 21 . Among the signaling pathways that are activated by the ROS are the Nuclear Factor Kappa B (NF-κB) and the mitogen activated protein kinase (MAPK) pathways that control diverse cellular events such as inflammation, proliferation and apoptosis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Brain natriuretic peptide (BNP) and N -terminal proBNP (NT-proBNP) are widely used as significant indicators for the clinical diagnosis of HF and cardiac dysfunction [11,12,13,14,15,16,17]. In recent years, many forensic studies have demonstrated that BNP and NT-proBNP could be used to reflect the cardiac function of the deceased before their death through extensive animal experiments and postmortem specimens, and they could also be used as postmortem biomarkers for the diagnosis of HF or cardiac dysfunction in forensic medicine [9,10,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The systemic effects of NPs are well described in the literature [9,10]. They are prevalently secreted in response to the mechanical stretch of myocardial walls induced by volume or pressure overload and then, once secreted, they exert diuretic, natriuretic, and vasodilatory effects, thereby maintaining cardio–renal homeostasis and hemodynamic status through the regulation of water–salt balance and body fluid volume [9,10,11]. NP secretion is also induced by other hormones, such as endothelin 1, angiotensin II, and by the adrenergic system [12,13,14].…”
Section: Introductionmentioning
confidence: 99%